Friends of Gustafson Gallery meeting - Unidentified photographer (Colorado State University. Libraries, 1991)
Photograph of several women at the Spring 1991 Friends of the Gustafson Gallery meeting. One woman is sitting on a chair, one woman is sitting on the floor, and three women are sitting on a couch. Two women are identified as Antigone Kotsiopulos and LaVon Blaesi.
Keywords: Fashion -- History; Fashion -- Exhibitions